The limitations of the hague convention to solve conflicts arising out of international child kidnapping - de Almeida, Wilson de Jesus Beserra; de Oliveira, Érico; Wang, Yong (Revista Brasileira de Direito, 2017)
Abstract: The present article aims to promote an analysis on the major Conventions concerning the removal and retention of children in different countries than theirs of habitual residence by one of the guardians, in particular the Hague Convention on the Civil Aspects of International Child Abduction, to discuss about the effectiveness on the application of its precepts. The study purposes to identify limitations and omissions in its text susceptible to undermine its applicability in practical cases. Key words: International parental child abduction. Private International Law. Principle of the best interests of the child. Hague Convention. Inter-American Convention.